(3cJGH aj GdUfYIs
(3ChdgG (B:s
(3GYde Cf GdeTGQ Edjg bWYI fGQ hPcQ ai MO GdPcQ hgGQH ONGf hdg RhLI HjVGA UGajI YSjQ QhMGfjI eGFjI dGjbOQ YdjgG GdGHQab GdMjd s
(3BNQgG (B:s
(3hdG cHQjJkG eMQbkG hdGjHGY hdGjTJQi eWgQ Yf cd fLS HOQI HjVGA jfMd HgG GdSMGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdNGeSs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdcjejGA h GdWHjYjGJs